Potret kenakalan remaja dalam novel dilan dia adalah dilanku karya pidi baiq - Diski Junaidi Putra; Yenni Hayati (BAHASTRA, 2020)
This study aims to describe juvenile delinquency in terms of the form, causes, and effects of delinquency carried out by adolescents contained in the novel Dilan Dia adalah Dilanku by Pidi Baiq. This type of research is a qualitative study using descriptive methods with data in the form of words, phrases, clauses, or sentences that indicate the problems of adolescent life in the novel. The results of this study prove that the novel shows juvenile delinquency and is depicted not much different from the reality of adolescent life today. Based on data analysis, juvenile delinquency contained in the novel is reviewed from (1) the form of juvenile delinquency in the form of delinquency that causes physical casualties, delinquency that results in material casualties, social delinquency that does not cause victims, delinquency which is against status; (2) the causes of juvenile delinquency in the form of negative nature that leads to damage, lack of self-control and social perception, inability to adapt to environmental changes, lack of creative hobbies or healthy hobbies, less effective supervision in coaching, lack of understanding of adolescents from the environment of adolescents, and family ignorance in dealing with adolescent problems; (3) the impact of juvenile delinquency in the form of adolescents themselves, for families, and for society.